Effect of Dietary Supplementation of Soapnut (Sapindus mukorossi) on Nutrient Utilization and Body Weight of HF Crossbred Cattle - Rathod, Sunil V; Pandya, Paresh R; Mathukiya, Gaurang P; Sorathiya, Kalpesh K (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was aimed to explore the effect of dietary supplementation of soapnut (Sapindus mukorossi) powder on nutrient  utilization and body weight (BW) in cattle. Fifteen HF crossbred cattle of same age and sex were divided into three equal groups on  the basis of BW and were offered three treatments for 70 days. The treatments were; T0: control TMR (roughage: concentrate ratio  65:35), T1: control TMR supplemented with 1% Soapnut powder, and T2: control TMR supplemented with 2% Soapnut powder. Among  the treatments BW gain observed was higher with lower level of soapnut supplement compared to higher soapnut level and control  diet. The study revealed no adverse effect of dietary supplementation of soapnut powder on dry matter and other nutrient intake. The  digestibility of nutrients was also not affected, except fibre fractions. Digestibility of CF, NDF and hemicellulose was adversely affected  by 2% followed by 1% soapnut powder supplementation in TMR over the control diet.
Keywords: Body weight; Cattle; Nutrient intake; Nutrient utilization